2017
DOI: 10.1177/0960327117698543
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and cigarette smoke modulate Nrf2-BDNF-dopaminergic signal and neurobehavioral disorders in adult rat cerebral cortex#

Abstract: Overall, our data strongly suggest that the intervention of DA and BDNF, and depletion of antioxidants are important factors during nicotine/CS-induced cerebral cortex pathological changes leading to neurobehavioral impairments, which could underpin the novel therapeutic approaches targeted at tobacco smoking/nicotine's neuropsychological disorders including cognition and drug addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…However, there were several limitations in this study. First, previous studies reported that exercise [ 42 ], smoking [ 43 ] and alcohol [ 44 ] were correlated with cognition. However, unfortunately, we did not collect the data for exercise level, smoking or alcohol drinking in our current study, which will be remedied in future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were several limitations in this study. First, previous studies reported that exercise [ 42 ], smoking [ 43 ] and alcohol [ 44 ] were correlated with cognition. However, unfortunately, we did not collect the data for exercise level, smoking or alcohol drinking in our current study, which will be remedied in future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, tobacco smoking cessation reduces risk for developing AD/ADRD (Choi et al, 2018). Tobacco smoke is a potent oxidative stressor (Pryor and Stone, 1993) that induces systemic oxidative stress (Sandhya et al, 2016) and depletes Nrf2 expression (Naha et al, 2018). Smoking-induced oxidative stress has been demonstrated in humans by quantifying a CSF biomarker, F2-isoprostane (iPF2α-III), levels of which are elevated in both cognitively normal elderly smokers and in probable AD smokers (Durazzo et al, 2014b(Durazzo et al, , 2016a.…”
Section: Tobacco Use Disordermentioning
confidence: 99%
“…Cytosolic enzymes such as xanthine oxidase (XO) during the catalytic oxidation of hypoxanthine to xanthine and Prostaglandin H Synthase (PHS) from arachidonic acid to prostaglandin generate ROS [ 24 ]. In addition, environmental pollutants; ionizing radiation (UV-rays, X-rays, γ-rays, and infrared or electromagnetic waves); smoking; long-term chemical exposure like pesticides, insecticides, or industrial solvents; heavy or transition metals (Cu, Fe, Mn, As, Cd, Pb, and Hg); diet; and physical exercise contribute to the production of ROS/RNS [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%